External therapy of traditional Chinese medicine for treating irritable bowel syndrome with diarrhea: A systematic review and meta-analysis - Wei, Xiuxiu; Wen, Yongtian; Wei, Yuchen; Liang, Xu; Ma, Xiangxue; Zhang, Beihua; Tang, Xudong (Frontiers in Medicine, 2022)
Background: Irritable bowel syndrome with diarrhea (IBS-D) is a chronic functional gastrointestinal disorder that has a significant impact on quality of life, work productivity, and healthcare resources. External therapy of traditional Chinese medicine (TCM) has positive effects on IBS-D and is simple, convenient, and low-cost. This study aimed to systematically evaluate the efficacy and safety of external therapy of TCM for IBS-D. Methods: This study was conducted according to PRISMA guidelines. PubMed, Embase, Cochrane Library, Web of Science, CNKI, VIP, Wan Fang, and CBM databases were electronically searched to collect randomized controlled trials comparing external therapy of TCM with Western medicine for IBS-D from inception to December 31, 2021. Two authors independently screened, extracted, and assessed the selected studies. The Jadad scale and Cochrane Collaboration Risk of Bias tool were used to evaluate the study quality. The certainty of the evidence was assessed using the grading of recommendations, assessment, development, and evaluations (GRADE). The meta-analysis was performed using Review Manager software (version 5.3). Results: Twenty-one studies involving 1862 subjects were included. Acupuncture and moxibustion were the most commonly used external therapies. A meta-analysis showed that, based on the total eﬀective rate with moderate certainty of evidence (RR=1.25, 95%CI [1.20, 1.31], I2=0%, P<0.00001), clinical cure rate with low certainty of evidence (RR=1.66, 95%CI [1.40, 1.96], I2=1%, P<0.00001), recurrence rate with very low certainty of evidence , total symptom score , and IBS-SSS with moderate certainty of evidence, the experimental group had significant advantages compared with the control group. A sensitivity analysis further confirmed the robustness of the primary outcomes. The improvement in quality of life associated with IBS (IBS-QOL) was superior in the experimental group compared to the control group, and the difference was statistically significant; however, the clinical heterogeneity was strong. The inverted funnel plot of the included studies indicated potential publication bias. Conclusions: External therapy of TCM for IBS-D alleviated abdominal symptoms, improved clinical effectiveness, and reduced recurrence with great safety. However, because of the limitations of publication bias in trials, more rigorous studies with a clinical design are necessary for further verification of these outcomes.